2024
DOI: 10.1186/s12891-023-07127-w
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic hand radiographs to screen for low forearm bone mineral density: a prospective and retrospective cohort study

Alana O’Mara,
Faes Kerkhof,
Deborah Kenney
et al.

Abstract: Background Low bone mineral density affects 53% of women over age 65 in the US, yet many are unaware and remain untreated. Underdiagnosis of forearm osteoporosis and related fragility fractures represent missed warning signs of more deadly, future fractures. This study aimed to determine if hand radiographs could serve as early, simple screening tools for predicting low forearm bone mineral density (BMD). Methods We evaluated posterior-anterior (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, recent studies have shown that after distal radius fracture, the incidence of hip and vertebral fractures increases by 1.51 times and 1.4 times, respectively. Moreover, reduced bone density in the distal forearm is linked to a higher risk of osteoporotic fractures [8,9]. Thus, evaluating bone density in the forearm can act as an independent risk factor for predicting future fractures and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies have shown that after distal radius fracture, the incidence of hip and vertebral fractures increases by 1.51 times and 1.4 times, respectively. Moreover, reduced bone density in the distal forearm is linked to a higher risk of osteoporotic fractures [8,9]. Thus, evaluating bone density in the forearm can act as an independent risk factor for predicting future fractures and mortality.…”
Section: Introductionmentioning
confidence: 99%